Position control for pulley axial movement of electro-mechanical dual acting pulley continuously variable transmission system. - Supriyo, Bambang; Tawi, Kamarul Baharin; Jamaluddin, Hishamuddin; Ariyono, Sugeng (Faculty of Mechanical Engineering, 2006)
Currently a hydraulic system has been used for changing Continuously Variable Transmission (CVT) ratio of metal pushing V-belt with single acting pulley system. This paper introduces an alternative way of changing CVT ratio using an electro-mechanical dual acting pulley (EMDAP) CVT system. This new system introduces two DC servomotors as actuators and power screw mechanisms as a means of shifting the pulleys axially along the transmission shafts. The primary motor is responsible for changing CVT ratio, while the secondary controls the metal belt from slipping. Since the methods of controlling these two motors are similar, this paper only discusses the primary part. The servomotor regulates the axial movement of two movable pulley sheaves to shift the metal belt placed between the sheaves, and change the belt-pulley contact radius. Changing this contact radius means changing the CVT ratio. Fuzzy PID control scheme is proposed for this pulley position control. Computer simulation results are presented to demonstrate the effectiveness of the proposed fuzzy PID controller as compared to that of the conventional fixed gain PID controller.